2017
DOI: 10.1007/s10886-017-0818-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Carbon Dioxide Concentration Reduces Alarm Signaling in Aphids

Abstract: Insects often rely on olfaction to communicate with conspecifics. While the chemical language of insects has been deciphered in recent decades, few studies have assessed how changes in atmospheric greenhouse gas concentrations might impact pheromonal communication in insects. Here, we hypothesize that changes in the concentration of atmospheric carbon dioxide affect the whole dynamics of alarm signaling in aphids, including: (1) the production of the active compound (E)-β-farnesene (Eβf), (2) emission behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…In the present study, we hypothesize that elevated CO 2 concentrations would impact the ability of an aphid predator to locate its prey and to thrive on its aphid diet. This hypothesis is based on several previously demonstrated facts: (i) E. balteatus larvae have very limited dispersal abilities, making the female's selection of an oviposition site essential for continuing its lineage (Verheggen et al ., ); (ii) hoverfly females rely on visual and volatile cues emitted by plants and aphids to select a suitable oviposition site (Almohamad et al ., ); and (iii) CO 2 concentration affects the semiochemistry of plants, aphids and aphid–plant interactions (Boullis et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, we hypothesize that elevated CO 2 concentrations would impact the ability of an aphid predator to locate its prey and to thrive on its aphid diet. This hypothesis is based on several previously demonstrated facts: (i) E. balteatus larvae have very limited dispersal abilities, making the female's selection of an oviposition site essential for continuing its lineage (Verheggen et al ., ); (ii) hoverfly females rely on visual and volatile cues emitted by plants and aphids to select a suitable oviposition site (Almohamad et al ., ); and (iii) CO 2 concentration affects the semiochemistry of plants, aphids and aphid–plant interactions (Boullis et al ., , ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we observe that the emission of Eβf is lower under elevated (eCO 2 ) conditions, which concurs with a recent study reported by Boullis et al . (). Because the size of our aphid colonies and the physiological status and experience of our experimental hoverflies is standardized, we suggest that only the aphid pheromone is responsible for the discriminating behaviour that we observe in ovipositing females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ocean acidification as a result of elevated CO 2 levels is reported to have reduced the olfactory response in a marine fish and disrupted its discriminatory ability (Munday et al, 2009). Also, the production and emission of alarm pheromone in an aphid, A. pisum, is reduced under elevated CO 2 (Boullis et al, 2017). Such results are suggested to be a result of the elevated CO 2 condition affecting the central nervous system (Mondor et al, 2004;Sun et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased CO 2 levels reduce the ability of a moth (Cactoblastis catorum) to detect host plants (Stange, 1997) and the escape behaviour associated with alarm pheromone is diminished under elevated CO 2 in the aphids Chaitophorus stevensis (Mondor et al, 2004), Sitobion avenae (Sun et al, 2010) and Amphorophora idaei (Hentley et al, 2014). Also, an increase in CO 2 concentration reduces the production and emission of alarm pheromone in the aphid species Acyrthosiphon pisum (Boullis et al, 2017). Because pheromones play a crucial role in mating, aggregation and alarm signals in insects (Rutowski, 1982;Cardé & Baker, 1984), an alteration in their communication system as a result of an increased CO 2 concentration will affect both mating and reproduction.…”
Section: Introductionmentioning
confidence: 99%